The Effect of Perceived Risks on Purchase Intention at UD. Kian Maju Medan: Pengaruh Perceived Risks Terhadap Minat Beli Pada UD. Kian Maju Medan - Albert; Elyzabeth Wijaya; Agus Susanto (Universitas Muhammadiyah Palu, 2023)
Perceived risk is a significant source of psychological stress that results in impaired purchase intention. Thus, marketers’ understanding of perceived risk structure and the provision of risk relievers give consumers a better environment for making purchase intentions. The writer conduct research at UD. Kian Maju Medan which engages in providing glassware and any other glassware products, the company is facing problem which customers experiences the functionality risks which fear that the product will fail to deliver based on its functions, the financial risks which the product’s quality doesn’t match its price, the prices that the company can change suddenly, customers have been spending much money on purchasing an inadequate or unfamiliar brand. The indicators of perceived risks were adopted from Bhukya and Singh (2015:221) which are perceived functional risk, perceived financial risk, perceived physical risk, and perceived psychological risk. The indicators of purchase intention are adopted from Elwanda and Lu (2012:7) which are product orders, customer satisfaction, loyalty, and repeat order. The population that the writer uses is the customers of UD. Kian maju Medan using Slovin’s formula get the sample size 81 people. The writer uses the simple random sampling which each member of the population has an equal and known chance of being selected. The results of calculations are perceived risks have effect on customer purchase intention which can be seen from hypothesis test (-zcount <-ztable), and perceived risks have a negative and strong effect on purchase intention from the result of correlation test, linear regression equation and determination test. Several recommendations are given based on the disagree answers of the respondents which make sure the quality of products to be high and standard quality that meet the customers’ needs, check and make sure the products are free from defects and chemicals, provide the well-known and familiar brand of products, and charge the prices based on the products’ materials.